(untitled) (Advances in Applied Biological Research, 2026)
Background and Rationale: Acute Myeloid Leukemia (AML) and Chronic Myeloid Leukemia (CML) are different blood cancers. They face critical treatment challenges, mainly drug resistance, such as the BCR-ABL1 T315I mutation, and the presence of Leukemic Stem Cells (LSCs). In India, CML occurs at a much younger age, creating an urgent need for cost-effective and safe alternatives to standard Tyrosine Kinase Inhibitors (TKIs). Research Aim: This study aims to use detailed computational (in-silico) methods to find and assess effective phytochemicals that can serve as multi-target inhibitors. The main goal is to discover natural compounds that can bypass known resistance mechanisms in CML and AML while effectively targeting pathways crucial for LSC survival, such as PP2A and HIF-1. Methodology: The research uses a high-throughput virtual screening strategy. Molecular docking simulations evaluate the binding strength and suitability of phytochemical libraries against key resistance targets (BCR-ABL1 T315I, FLT3) and LSC regulators. At the same time, we conduct ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) profiling and drug-likeness assessment (Lipinski’s Rule of Five) to prioritize compounds with good oral bioavailability and safety profiles suitable for long-term treatment. Conclusion: This study applies polypharmacology to demonstrate how phytochemicals can function as effective multi-target therapeutic leads. By moving beyond the traditional “one-drug-one target” approach, these natural bioactive compounds provide a strategic way to bypass drug resistance and eliminate the resilient leukemic stem cell populations that drive relapse in AML and CML.